Physiological Effects of Local Theragun™ Application: An Observational Study in Healthy Female Participants - Ron Clijsen; Livia Freitag; Erich Hohenauer; Giannina Bianchi (International Journal of Sports Physical Therapy)
# Background While the clinical effects of localized percussive therapy (PT) are well-documented, studies investigating the underlying physiological mechanisms remain scarce. # Purpose The aim of this study was to investigate the changes and time course of local skin temperature (Tskin), deep tissue perfusion (erythrocyte flow velocity [speed] and deep tissue blood flow [flux]), and muscle oxygenation (SmO2) after a standardized 4-minute treatment with a TheragunTM of the vastus medialis muscle of healthy women. # Study design Descriptive Laboratory Study. # Methods Tskin, speed, flux and SmO2 were measured in the treated area in 26 healthy female participants at baseline and following a 4-minute TheragunTM application, with recordings taken at 5-minute intervals for up to 50 minutes post-application. Additionally, Tskin was also measured on the control leg. A repeated measures ANOVA was performed to assess temporal changes and differences between the treated and control conditions. # Results Following the Theragun™ treatment, significant increases were observed in the treated area at all time points for Tskin (p < 0.001), speed (p < 0.001), flux (p < 0.001), and SmO2 (p < 0.05) compared to baseline. Tskin (mean change of 3.76 °C) and SmO2 (mean change of 5.78%) reached their highest values at five minutes post-treatment (t5), whereas speed (mean change of 23.79 arbitrary units [AU]) and flux (mean change of 115.66 AU) peaked immediately (t0) after the application. Tskin on the control leg also differed significantly across all time intervals compared to baseline (p < 0.05), peaking at t30 (mean change 0.64°C). # Conclusion A 4-minute localized Theragun™ application enhances physiological responses in cutaneous, subcutaneous, and muscle tissues. It increases skin temperature and improves deep tissue blood flow, red blood cell movement, and muscle oxygenation. These findings highlight the impact of TheragunTM on deep tissue layers, offering valuable insights into the physiological mechanisms of PT. The results support the potential for its use in optimising athletic performance and recovery through enhanced blood flow and muscle oxygenation.